CEO compensation in relation to worker compensation across countries: The configurational impact of country‐level institutions - Greckhamer, Thomas (Strategic Management Journal, 2016)
Executive compensation and its relation to that of rank and file employees are vital areas of strategy research. This study contributes to our understanding of cross‐national differences in executive compensation by exploring how key formal and informal country‐level institutions of social power structures combine to shape CEO and worker compensation across countries as well as the resulting pay dispersion. Analyzing data spanning 54 countries using the configurational approach f uzzy s et Q ualitative C omparative A nalysis ( fsQCA ), the study also explores the causal asymmetry underlying compensation outcomes by investigating institutional configurations linked to high CEO compensation, high worker pay, and high pay dispersion and those configurations linked to the absence of these outcomes. The article concludes by discussing the study's implications for theory and research on executive compensation . Copyright © 2015 John Wiley & Sons, Ltd.